Narrative structure, context and translation in Paulo Coelho's O Alquimista in English, Arabic and Turkish. (2nd January 2016) - Aljahdali, Sawsan A.
Abstract : The contentious bestsellerdom of Coelho's O Alquimista (published in 1988) has not only placed it endurably on top of the prestigious bestseller lists, but also made it subject to severe criticism. With copyrights sold in 80 languages, the narrative creates a unique form of communication implementing a prolonged, interactive language–culture relationship, and recreating appealingly unique narrative structures addressing readers in new contexts. This study attempts a functional semantico–semiotic reading of the narrative structures of O Alquimista in English, Arabic and Turkish, relating the "recreated texts" to their sociocultural "context of interpretation", and viewing them as the outcome of two separate acts of communication functioning successively on the same semantic content . The study argues that rediscoursing the narrative cross-culturally yields variant narrative structures, each constructed twice– internally, in the act of encoding through writing, and externally through the reader–text interaction in reading.